Razgradnja ksilana z različnimi ksilanazami vampne bakterije Pseudobutyrivibrio xylanivorans Mz5T - Čepeljnik, Tadej (Acta agriculturae Slovenica, 2004)
The use of xylanases as feed additives for monogastric animals is very promising. Many experiments have proved their beneficial effect on animal health and performance. A new rumen bacterium species has recently been isolated: P. xylanivorans, type strain Mz5T, which has a very high xylanolytic activity. Some of its xylanolytic enzymes have already been described. We want to analyse the rest of them to find the reason for its high xylanolytic activity and to assess the possibilities of using this bacterium as a probiotic for monogastric animals (pigs, poultry) or its enzymes as feed additives. We have partially isolated two xylanases from the cell extract: 44 kDa and 81 kDa and examined their properties. We also compared enzyme activities of cell surface xylanases with xylanases in cell extract. The 44 kDa xylanase is an exoxylanase without ß-xylosidase activity. We assume that the 81 kDa xylanase is an endoxylanase. Xylanolytic enzymes on the cell surface are efficient xylan degraders, but they are unable to degrade xylobiose. Xylobiose is degraded by xylanolytic enzymes inside the cell.
Keywords: microbiology; mikrobiologija; anaerobne bakterije; ksilanaze; encimi; prebava; krma; vamp